UJI AKTIVITAS TABIR SURYA PADA EKSTRAK HERBA SURUHAN (Peperomia pellucida [L.] Kunth) DAN OKTIL METOKSISINAMAT - Pratiwi, Inda; Djamil, Ratna; Noor, Siti Umrah (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2024)
Herba suruhan (Peperomia pellucida [L.] Kunth) is a plant that contains flavonoids, functioning as a sunscreen. Octyl methoxycinnamate (OMC) is a synthetic compound used in cosmetic products as a sunscreen ingredient. The purpose of this study was to determine the sunscreen activity by determining the SPF value of the extract of herba suruhan (Peperomia pellucida [L.] Kunth) with octyl methoxycinnamate singly. Herba suruhan was extracted by UAE method and then calculated the SPF value of herba suruhan extract with concentrations of 0.06%, 0.07%, 0.08%, 0.09% and 0.1% and the SPF value of octyl methoxycinnamate with concentrations of 1%, 2.5%, 5% and 7.5%. The results of SPF values of Chinese betel herb extract with concentrations of 0.06%, 0.07%, 0.08%, 0.09% and 0.1% were 22, 24, 30, 33 and 39 respectively. The SPF values of octyl methoxycinnamate with concentrations of 1%, 2.5%, 5% and 7.5% were 39, 39, 40 and 40 respectively. The highest SPF value of betel herb extract at a concentration of 0.1% is 39 and octyl methoxycinnamate at a concentration of 5% and 7.5% is 40. Keywords: Peperomia pellucida [L.] Kunth, Octyl methoxycinnamate, sunscreen